179 A Comparison of Local Anesthetic Effectiveness in Reducing Pain Associated with Dehorning in Dairy Calves. (7th May 2021) - Martin, Miriam S; Kleinhenz, Michael; Viscardi, Abbie; Curtis, Andrew; Johnson, Blaine; Montgomery, Shawnee; Coetzee, Johann
Abstract: Dehorning is performed on a high percentage of dairies in the United States. Concern for animal welfare has led to investigating pain mitigation during dehorning. The objective was to compare the effectiveness of bupivacaine liposome suspension, lidocaine, or lidocaine + meloxicam administered at dehorning. Fifty male Holstein calves, 10–14 weeks of age were enrolled and randomly assigned to 1 of 5 treatment groups: 1) bupivacaine liposome suspension block, oral placebo, cautery dehorn (BUP); 2) lidocaine block, oral placebo, cautery dehorn (LID); 3) lidocaine block, oral meloxicam, cautery dehorn (LID + MEL); 4) saline block, oral placebo, cautery dehorn (CON); and 5) saline block, oral placebo, sham dehorn (SHAM). Biomarkers were collected from 0 to 120 hours post-dehorning and included infrared thermography (IRT), mechanical nociceptive threshold (MNT), and pressure mat gait analysis. Biomarkers were statistically analyzed using repeat measures with the calf being the repeated measure. There were no significant treatment differences for IRT measures. A treatment effect was observed for the mean difference of the right horn bud minus a control point which were -1.21 kgF, -1.41 kgF, -1.56 kgF, -1.65 kgF, and -1.68 kgF for the SHAM, CON, BUP, LID + MEL, and LID groups, respectively (P = 0.004). The BUP group did not differ from CON (P = 0.78) or SHAM (P = 0.07). A treatment effect was observed for gait distance means which were 182.05 cm, 189.69 cm, 195.77 cm, 199.54 cm, and 200.59 cm for the SHAM, BUP, LID + MEL, LID and CON groups, respectively (P = 0.04). The CON group did not differ from BUP, LID, or LID + MEL (P > 0.05) but did differ from SHAM (P = 0.02). These data show that administration of bupivacaine liposome suspension at the time of dehorning was not different than lidocaine or lidocaine + meloxicam.